2018
DOI: 10.3844/ajbbsp.2018.200.209
|View full text |Cite
|
Sign up to set email alerts
|

Mining, Isolation and Identification of Siderophore Synthesis Gene from Brevibacillus brevis GZDF3

Abstract: Objective of this paper is to excavate the siderophore synthesis gene from Brevibacillus brevis GZDF3 and verify its type and antibacterial effects. The method is using genome mining technology to analyze the siderophore synthesis genes and the phylogenetic tree of each synthesis gene was constructed separately. Iron free medium was utilized to induce the synthesis of siderophore and CAS liquid detection method was used for qualitative and quantitative analysis on siderophore. The type of siderophore was preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The siderophore production was determined by CAS liquid test. The cell growth and siderophore production were measured as a function of fermentation time at 0, 6,12,18,24,30,36,42,48,54, and 60 h. The pH was adjusted to 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, and 10.0, respectively. Fermentation temperature was set from 23°C to 37°C.…”
Section: Optimization Of the Cultural Conditions For Siderophore Prodmentioning
confidence: 99%
See 1 more Smart Citation
“…The siderophore production was determined by CAS liquid test. The cell growth and siderophore production were measured as a function of fermentation time at 0, 6,12,18,24,30,36,42,48,54, and 60 h. The pH was adjusted to 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, and 10.0, respectively. Fermentation temperature was set from 23°C to 37°C.…”
Section: Optimization Of the Cultural Conditions For Siderophore Prodmentioning
confidence: 99%
“…Our previous research reported that B. brevis GZDF3 can produce catechol-type siderophores and has a strong antagonistic effect on F. oxysporum . However, factors that affect the production of siderophores and the antifungal effect against Candida albicans of B. brevis GZDF3 have not yet been reported [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that B14 strain carried entD gene which encodes a product necessary for the synthesis of the iron-chelating and transport siderophore enterobactin (Khan et al 2018), while the genome of B19 contained asbF gene involved in 3,4-dihydroxybenzoic acid synthase that is necessary for petrobactin production (Hotta et al 2010). Previous studies indicated that Brevibacillus brevis showed strong antagonistic effect against F. oxysporum and siderophore synthesis gene cluster with 83 % similarity to petrobactin was found in the genome of this strain (Sheng et al 2018).…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, both KEGG Mapper and antiSMASH analysis of the K75 genome revealed the presence of a gene involved in the synthesis of petrobactin, and in vitro assay showed a strong ability to produce siderophores by B. lateropsorus K75. Sheng et al 47 reported that B. brevis GZDF3 had strong antifungal activity, and a siderophore synthesis gene cluster that was 83% similar to petrobactin was annotated in the genome. Moreover, other biosynthetic gene clusters involved in antimicrobial compounds synthesis were found.…”
Section: Discussionmentioning
confidence: 99%